The Effect of Learning and Development Programs, Digital Communication Platforms, and Performance Management Systems on Employee Productivity in Digital Work Environments in Indonesia - Syamsulbahri, Syamsulbahri; Bardai, Borjoyai (Eastasouth Institute, 2025)
This study investigates the effects of Learning and Development Programs, Digital Communication Platforms, and Performance Management Systems on Employee Productivity in Indonesian digital workplaces. The quantitative approach was utilized with a sample of 200 employees using a Likert scale (1-5). Structural Equation Modeling - Partial Least Squares (SEM-PLS) was utilized for data analysis. Results show that all three variables significantly and positively impact employee productivity, with the greatest effect seen in Digital Communication Platforms. The model explains 72% of the variance in productivity, as it underscores the necessity for end-to-end strategies integrating employee development, communication tools, and performance systems to boost productivity. Such findings have practical and theoretical consequences for fostering efficiency in the digital workplace.